INFLUENCE OF MAN-MACHINE RATIO ON SYSTEM PERFORMANCE OF ONE-PERSON-MULTI-MACHINE SERIES PRODUCTION LINE - Zhou, Yu; Kong, Fansen; Chen, Taibo (International Journal of Industrial Engineering: Theory, Applications and Practice, 2021)
The one-person-multi-machine assignment is a typical feature of lean production systems. The major disadvantage of this type of assignment is that it could cause system delay due to human failure. Therefore, it is important to analyze the degree of efficiency loss among machines caused by interference between operators and machines. In this paper, a methodology is developed based on the decomposition technique. The whole U-shape production line is modeled as several subsystems where the efficiency loss mentioned above can be treated as machine failure. Hence, each subsystem can be simplified as an unreliable workstation with a certain failure rate. With finite buffers between consecutive subsystems, the influence of human failure can be analyzed and verified with an industry-based case study. Data was collected from an automotive electronics plant as well as corresponding computational and simulation test results. Statistics show that the method developed in this paper will make contributions to solving industrial problems.